2015
DOI: 10.1002/he.20154
|View full text |Cite
|
Sign up to set email alerts
|

Increasing College Completion for Latino/as in Community Colleges: Leadership and Strategy

Abstract: This chapter discusses college completion for Latino/as who attend community colleges and the role of leadership in promoting completion. The chapter also provides a number of lessons for success drawn from the national initiative, Achieving the Dream.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 14 publications
0
10
0
Order By: Relevance
“…Researchers and practitioners describe the transfer pathway in California as "log-jams," "puzzles," and "labyrinths" (Dowd, 2007;Jain et al, 2020;Martinez-Wenzl & Marquez, 2012). Unclear transfer pathways from community college to 4-year institutions jeopardize the ability of California's students, notably Latinx students, from achieving a Bachelor's degree (Contreras & Contreras, 2015;Gonzalez, 2015).…”
Section: Latinx Students the Transfer Process And Educational Inequitiesmentioning
confidence: 99%
“…Researchers and practitioners describe the transfer pathway in California as "log-jams," "puzzles," and "labyrinths" (Dowd, 2007;Jain et al, 2020;Martinez-Wenzl & Marquez, 2012). Unclear transfer pathways from community college to 4-year institutions jeopardize the ability of California's students, notably Latinx students, from achieving a Bachelor's degree (Contreras & Contreras, 2015;Gonzalez, 2015).…”
Section: Latinx Students the Transfer Process And Educational Inequitiesmentioning
confidence: 99%
“…Franklin, Smith, and Hung (2014) found that racialized and microaggressive incidents on college campuses lead to emotional and psychological fatigue among minority students. As a result, minority students, particularly Latinx and African American students, have lower rates of academic persistence and graduation than their majority peers (Contreras, 2009; Crisp et al., 2015; González, 2015; Tajalli & Ortiz, 2018).…”
Section: Study Purpose and Overviewmentioning
confidence: 99%
“…For example, community college presidents must ensure the institution adapts to the students they serve rather than forcing the students to change to fit the institution (Eddy, 2010;Gonzalez, 2015).…”
Section: Community College Presidential Leadership and The Degree Commentioning
confidence: 99%
“…Recently, policymakers have been incorporating degree completion rates as a performance metric through performance-based funding policies to pressure higher education institutions to increase degree completion rates (Gonzalez, 2015). This recent focus on the degree completion agenda may require community college presidents to implement institutional policies to address the external demands of improving degree completion rates, which may be at the expense of other pressing institutional goals (e.g.…”
Section: Community College Presidential Leadership and The Degree Commentioning
confidence: 99%
See 1 more Smart Citation